Analyzing KH Ahmad Dahlan's Ideas on Progressive Islamic Education within the Muhammadiyah Framework - Tentiasih, Septyana; Khozin, Khozin; Hakim, Nur (Institut Agama Islam Negeri (IAIN) Manado, 2023)
Progressive Islam in Muhammadiyah is not to make Islam more advanced, but rather the meaning of progressive Islam is to strengthen the Islamic faith, even though over time, people's beliefs have changed, poisoned by many new ideologies. The purpose of this research is to determine the concept of progressive Islamic education and KH Ahmad Dahlan's thoughts on progressive Islamic education. The research method used is library research, which is a means of finding information or data from scientific papers, book review articles, and literature sources. The sources used in this research are obtained from various books, journals, and other research results such as (theses and dissertations) as well as other sources from the results of tarjih decisions and Muhammadiyah congresses. The results of this study contain that the concept of progressive Islamic education can be understood as Islamic education in which there is a renewal of one's way of thinking or perspective on the development of science and its application to teachers. Meanwhile, KH Ahmad Dahlan's thought regarding the concept of progressive Islamic education is that progressive education does not only emphasize the doctrine of religious (Islamic) pedagogy, but also contains the mission of achieving social pedagogy by providing quality education to all people in Indonesia. This is evidenced by the presence of Muhammadiyah educational institutions in Islamic areas as well as for religious minority believers.